Chapter Atmospheric agents and spatial planning. Case study of the municipality of Rosignano Marittimo in Tuscany - Saragosa, Claudio (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
In recent years, Tuscan coastal areas have been repeatedly affected by more and more intense weather phenomena, which have caused damage to people and urban settlements. Extreme weather events such as intense downpours, floods, whirlwinds and powerful sea storms, together with critical issues due to ongoing coastal erosion, highlight a number of problems.The physical definition of the coastal system and the management definition of same are topics that sets the goal of defining a possible methodological approach through the presentation of the case study for territorial planning.